Manajemen Risiko Pembiayaan Murabahah Perbankan Syariah - Rohmaniyah, Hibatur; Fathony, Alvan (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2021)
Background. Islamic banking faces the challenges of developing an increasingly complex and risky external and internal situation in business. Islamic banking needs to implement risk management, which will have an impact on both banks and banking supervisory authorities. Aim. This research was conducted to determine how the an operational steps of Murabahah financing, to find out the obstacles associated with Murabahah financing and how the risk management of Islamic banking was in overcoming the constraints that occurred both internal or external constraints on Murabahah financing. Methods. This research uses a normative legal research method, which is carried out by conducting library research on a various relevant legal materials, both through a primary legal materials, which are obtained from a number of laws and regulations. Results. The results of this study indicate that Murabahah financing in Islamic banking is the financing that is most in demand by the public with a low indene of a risks, however, the risks management is still used to further minimize the occurrence of a greater risks.